Structure and History - Greimas, Algirdas Julius (Problemos, 1974)
A. J. Greimas, a noted semanticist, investigates in his paper the possibility of applying structural principles to the description of history, generalizes and critically evaluates current structuralist tendencies to link structure with history. The definition of the relation between structure and history, in A. J. Greimas’ view, depends on the answer one gives to these two questions: a) how does historicity or social structures manifest itself; b) how should one define diachronic transformations between structures following one another in time? It is held that social structure possesses a number or combinatorial possibilities, though only a few of them are realized in actual history (e.g., the structure of feudalism has different manifestations such as the French, Japanese or Judean feudalism). Therefore history is closed, for it blocks the way to new meanings existing virtually in the structure on which it depends. It is assumed at the same time that the originality of diachronic transformations consists in their irreversible character. If a definite type of correlations could be determined allowing us to state that in case of two structures s1 and s2 and their correlation R, structure s2 can be a transform of structure s1 and not vice versa, then the problem of diachrnnic transformations could be solved. But such rules are not known yet.